ALK‐rearrangement in non‐small‐cell lung cancer (NSCLC). Issue 4 (28th February 2018) - Du, Xue; Shao, Yun; Qin, Hai‐Feng; Tai, Yan‐Hong; Gao, Hong‐Jun
Abstract : The ALK gene encodes a transmembrane tyrosine kinase receptor. ALK is physiologically expressed in the nervous system during embryogenesis, but its expression decreases postnatally. ALK first emerged in the field of oncology in 1994 when it was identified to fuse to NPM1 in anaplastic large‐cell lymphoma. Since then, ALK has been associated with other types of cancers, including non‐small‐cell lung cancer (NSCLC). More than 19 different ALK fusion partners have been discovered in NSCLC, including EML4, KIF5B, KLC1, and TPR . Most of these ALK fusions in NSCLC patients respond well to the ALK inhibitor, crizotinib. In this paper, we reviewed fusion partner genes with ALK, detection methods for ALK ‐rearrangement ( ALK ‐R), and the ALK‐tyrosine kinase inhibitor, crizotinib, used in NSCLC patients.